Things that Grow - Goldstein, Meredith (Boston : Houghton Mifflin Harcourt, 2021)
"After her grandmother dies, a girl travels to different gardens to scatter her ashes, learning about life and love along the way."--Provided by publisher.
Keywords: Grandmothers -- Juvenile fiction -- Death; Automobile travel -- Juvenile fiction; Bildunsromans; Grandmothers -- Fiction -- Death; Automobile travel -- Fiction; Coming of age -- Fiction; Young adult fiction